The CYP17 and CYP19 gene single nucleotide polymorphism in women with sporadic breast cancer - Sobczuk, Anna; Romanowicz, Hanna; Fiks, Tomasz; Połać, Ireneusz; Smolarz, Beata (Polish Journal of Pathology, 2009)
The cytochrome P450 family (CYPs) enzymes play an important role in the metabolism of environmental carcinogens and of oestrogen and can affect breast cancer risk. We hypothesise that polymorphisms of CYP17 and CYP19 gene can predict higher incidence of breast cancer. In the present work the distribution of genotypes and frequency of alleles of the T/C polymorphism in promoter region of CYP17 and Trp/Arg polymorphism in codon 39 of CYP19 gene in breast cancer women were investigated. The genetic polymorphisms analysis was performed by amplifying DNA by PCR-RFLP methods in 100 sporadic breast cancer cases. The distribution of the genotypes of the T/C polymorphism of CYP17 in patients differed significantly (p < 0.05) from those predicted by the Hardy-Weinberg equilibrium. There were significant differences in the frequencies of alleles between the breast cancer subjects and controls (p 0.05) from those predicted by the Hardy-Weinberg distribution. The results support the hypothesis that the T/C polymorphism of CYP17 gene may be associated with the incidence of breast cancer in women from Lodz region of Poland.